S130 Preliminary data supporting a 'direct to lat' strategy in selected patients with suspected malignant pleural effusion. (15th November 2017) - Tsim, S; Paterson, S; Holme, J; Evison, M; Blyth, KG
Abstract : Introduction: Malignant Pleural Effusion (MPE) requires a rapid and precise pathological diagnosis. However, the diagnostic yield of pleural fluid cytology is only 60%, varying by tumour type and is effectively 0% in Malignant Pleural Mesothelioma (MPM) in most centres. BTS guidelines recommend pleural fluid cytology prior to Local Anaesthetic Thoracoscopy (LAT), often resulting in pathway delay, without diagnostic value, in patients with symptomatic effusion. Pathway rationalisation requires data to support a 'direct to LAT' strategy, which may be appropriate in carefully selected patients. Methods: 466 patients with suspected MPE, recruited to the prospective, multi-centre DIAPHRAGM study (ISRCTN10079972 ) in Glasgow and South Manchester, were selected. All data was recorded prospectively except CT reports, which were retrieved retrospectively from electronic records. Cases were classified into 'benign' and 'malignant' CT groups (using previously published criteria (Hallifax et al 2014, Tsim et al 2016), and asbestos-exposed and non-exposed groups. The diagnostic performance of pleural cytology was compared based on these features. Results: 36/466 (8%) were excluded (non-contrast CT (n=15), non-contiguous CT (n=5), no definitive diagnosis (n=16)). In the remaining 430 cases, median age was 73 (IQR 66–80) years. 264/430 (61%) were diagnosed with MPE, of whom 107 (41%) had MPM. Median time from pleural aspiration to cytology report was 6 (4 -9) days. Median time from pleural aspiration to pleural biopsy was 20 (12 – 36) days. 189/430 (44%) were asbestos-exposed. 189/430 (44%) had a 'malignant' CT report. The diagnostic performance of pleural cytology based on combinations of these features is summarised in Table 1 . In patients with MPE, the majority of patients with benign or non-diagnostic cytology had MPM (92/152 (61%)), particularly in asbestos-exposed patients (69/79 (87%)). Conclusions: Pleural cytology is frequently unhelpful in patients with MPE. The sensitivity and negative predictive value of pre-LAT aspiration cytology appears particularly low in patients with CT evidence of pleural tumour and a history of asbestos exposure, reflecting a higher prevalence of MPM. A 'direct to LAT' strategy, assuming pleural chemistry and microbiology suggest a sterile exudate, may be appropriate in these cases. However, a prospective study would be required to validate such an approach.